Implementasi Kebijakan Surabaya Cross Culture International sebagai Upaya Pengembangan Pariwisata di Kota Surabaya - Hikmah, Dzakiyah Adalatul; Khusnul Prasetyo; Eka Arum Pramestya (Universitas Brawijaya, 2022)
Every government, regardless of size, must constantly adapt to a changing environment and direct a change in a positive direction in which development is a key to do so. The tourism industry is one of the few development fields that has consistently excelled. The purpose of the Surabaya City Tourism and Culture Office, which bears the nickname